Inclusion of People Poststroke in Cardiac Rehabilitation Programs in Canada: A Missed Opportunity for Referral - Toma, Jelena (CJC Open, 2020)
BACKGROUND: Evidence supports establishing a continuum of care from stroke rehabilitation (SR) to cardiac rehabilitation programs (CRPs). It is not known to what extent people poststroke are being integrated. This study aimed to determine the proportion of CRPs that accept referrals poststroke, barriers/facilitators, and eligibility criteria. METHODS: A web-based questionnaire was sent to CRPs across Canada. RESULTS: Of 160 questionnaires sent, 114 representatives (71%) of 130 CRPs responded. Of respondents, 65% (n = 74) reported accepting people with a diagnosis of stroke and doing so for a median of 11 years, 11 offering stroke-specific classes and an additional 6 planning inclusion. However, 62.5% of CRPs reported that < 11 patients participated in the last calendar year despite 88.5% reporting no limit to the number they could enroll. Among CRPs, 25% accepted only patients with concurrent cardiac diagnoses, living in the community (47.8%), and without severe mobility (70.1%), communication (80.6%), or cognitive (85.1%) deficits. The 2 most influential barriers and facilitators among all CRPs were funding and staffing. The fourth greatest barrier was lack of poststroke referrals, and third to sixth facilitators were SR/CRP collaboration to ensure appropriate referrals (third) and to increase referrals (sixth), toolkits for prescribing resistance (fourth), and aerobic training (fifth). CRP characteristics associated with accepting stroke were a hybrid program model, a medium program size, and having a falls prevention component. CONCLUSIONS: Most CRPs accept patients poststroke, but few participate. Therefore, establishing SR/CRP partnerships to increase appropriate referrals, using a toolkit to help operationalize exercise components, and allocating funding/resources to CRPs may significantly increase access to secondary prevention strategies.